PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN - Indah Dwi Jaya; Deskoni (Journal of Practice Learning and Educational Development, 2026)
This study examines the effect of Quizwhizzer, a web-based interactive learning platform, on students’ learning motivation in Economics at SMA Negeri 12 Palembang. Using a quantitative approach with a pre-experimental One Shot Case Study design, the research involved 33 students from class XI.4 as participants. Data were collected through a 30-item learning-motivation questionnaire and structured classroom observations aimed at capturing students’ behavioral and affective engagement. The findings indicate a substantial improvement in learning motivation following the implementation of Quizwhizzer. The mean motivation score increased from 77.23% at the pre-treatment stage to 85.24% at the post-treatment stage, with all students falling into the “good” to “very good” categories after the intervention. Observational results further reinforce these findings by showing noticeable growth in students’ activeness, concentration, enthusiasm, and readiness to participate during the learning process. These outcomes highlight the effectiveness of Quizwhizzer’s gamification features—such as points, leaderboards, and real-time feedback—in stimulating students’ intrinsic motivation and creating a more dynamic and enjoyable learning environment. Overall, the study concludes that Quizwhizzer is a highly beneficial digital learning medium that enhances student motivation and supports more interactive, engaging, and relevant Economics instruction in the digital era.